Наконечники метательного вооружения у охотников на бизона Северо-Западного Причерноморья (на примере археологической коллекции верхнепалеолитического поселения Анетовка ІІ) - Пиструил, И.В. (Материалы по археологии Северного Причерноморья, 2019)
Позднепалеолитическое поселение охотников на бизона Анетовка ІІ обнаружено в 1978 г. и систематически исследуется 40 лет Причерноморской экспедицией под руководством В.Н. Станко. Поселение расположено на мысу правого берега реки Бакшалы, притока Южного Буга, на площадке третьей надпойменной террасы, слегка покатой к реке, на юго-западной окраине села Анетовка Доманевского района Николаевской области. Arrowheads of throwing weaponry of bison hunters of North-west Pontic region (archaeological collection of Upper Palaeolithic settlement of Anetovka ІІ) The paper presents the analysis of possible variants of flint bladelets attachment to arrowheads of throwing weaponry employed by Upper Palaeolithic herd animals hunters of North-west Pontic region. Available archaeological material (numerous flint, bone and antler artifacts) is the result of over 30-year excavations of Upper Palaeolithic settlement of Anetovka ІІ. Backed microblades and micropoints prevail among flint artifacts with secondary treatment and were used for throwing weaponry arrowheads equipment. Items of hunting weaponry (arrow-, dart- and spear-points) constitute the most numerous group among bone and antler artifacts. The artifact collection includes also one arrowhead with precisely slotted grooves. Research author (V.N. Stanko) considered these grooves to be cannelures for blood flow; according to opposite opinion (I.V. Sapozhnikov) grooves functioned for inserts attachment, and there must be more such grooved arrowheads in archaeological collection of Anetovka ІІ. The undertaken analysis led to conclusion that purposefully slotted grooves had no function of microliths attachment, whereas backed microblades and micropoints were fixed directly to arrowhead surface by means of organic resin.